Atherosclerosis in intracranial, extracranial, and coronary arteries with aortic plaques in patients with ischemic stroke of undetermined etiology - Chatzikonstantinou, Anastasios; Ebert, Anne; Schönberg, Stefan; Hennerici, Michael G.; Henzler, Thomas (The international journal of neuroscience, 2015)
Objective: We investigated the association of cerebral and coronary artery atherosclerosis with the presence, burden and type of atherosclerotic plaques of the aorta (AP) in patients with ischemic stroke of undetermined etiology. Methods: 48 consecutive patients (32 males, mean age 68±11 years) with acute ischemic stroke of unknown etiology after thorough stroke workup were investigated using ECG-gated CT-Angiography (CTA) for the detection of embolic AP. Intima media thickness (IMT), presence of carotid plaques and stenosis ≥50% and intracranial stenosis were assessed as parameters of cerebral atherosclerosis, the Agatston score (AS) and coronary artery stenosis ≥50% (CAS) in CTA as parameters of coronary atherosclerosis. Plaque burden was classified as mild or severe and plaque types were classified according to their morphology in calcified, non-calcified or mixed. Results: APs were found in 36 patients (75%). AP presence was associated with higher IMT values (p = 0.029), intracranial stenosis (p = 0.047), CAS (p = 0.033) and AS (p = 0.026). Twenty-three of 31 (74.2%) patients with both carotid atherosclerosis and AP revealed plaque calcification (p = 0.041). Ten of 14 (71.4%) patients with AP and intracranial stenosis had calcified plaques (p = 0.030). AP in more than one aortic segment was found in patients with bilateral carotid stenosis ≥50% (p = 0.038), intracranial stenosis (p = 0.042), high IMT (p = 0.040) and higher AS (p = 0.019). Conclusions: Aortic atherosclerotic plaques are common in patients with ischemic stroke of undetermined etiology and in particular those with carotid, intracranial and coronary atherosclerosis or high IMT values. In these patients, CTA of aorta should be seriously considered.